Ti1-xAgx and Ag-TiNx coatings deposited on PVDF substrates for sensors applications - Marques, S. (2017)
[Excerpt] Electroactive polymers are the most interesting class of polymers used as smart materials in various applications, such as the development of sensors and actuators for biomedical applications in areas as smart prosthesis, implantable biosensors and biomechanical signal monitoring, among others. The aim of this work was the development of multifunctional coatings on a polymeric base substrate for biosensor applications. The coatings were deposited by magnetron sputtering on polymers based sensors and the different processing conditions allowed to obtain two different systems: Ti1-xAgx with different Ag/Ti atomic ratio and different Ag-TiNx samples with increasing N content. These electrodes were deposited at room temperature on poly(vinylidene fluoride), PVDF. Only on Ag-TiNx electrodes it was possible to found Ag clusters. [...]